How do you solve (x - 2)/( x + 1) =( x + 1)/(x - 2)?
2 Answers
Jun 19, 2016
Explanation:
Cross multiply the terms,
If both x-2 and x+1 are positive or negative, then this has no solution.
If x+1 is negative, then x-2 is also negative. (
So our only option is if x-2 is negative and x+1 is positive.
In this case,
We have,
Jun 19, 2016
Explanation:
Given:
(x-2)/(x+1) = (x+1)/(x-2)
Multiply both sides by
(x-2)^2 = (x+1)^2
Expanding both sides this becomes:
x^2-4x+4 = x^2+2x+1
Subtract
-4x+4 = 2x+1
Add
4 = 6x+1
Subtract
3 = 6x
Divide both sides by
x = 1/2